Neck Infection Associated with Pyriform Sinus Fistula: Imaging Findings - Park, Sun-Won (AJNR Am J Neuroradiol, 2000)
BACKGROUND AND PURPOSE: Acute suppurative neck infections associated with branchial fistulas are frequently recurrent. In this study, we describe the imaging findings of acute suppurative infection of the neck caused by a third or fourth branchial fistula (pyriform sinus fistula). METHODS: Imaging findings were reviewed in 17 patients (11 female and six male patients, 2 to 49 years old) with neck infection associated with pyriform sinus fistula. Surgery or laryngoscopic examination confirmed the diagnoses. Fourteen patients had a history of recurrent neck infection and seven had cutaneous openings on the anterior portion of the neck (all lesions were on the left side). Imaging studies included barium esophagography (n = 16), CT (n = 14), MR imaging (n = 2), and sonography (n = 3). RESULTS: A sinus or fistulous tract was identified in eight of 16 patients on barium esophagograms. In 14 patients, CT studies showed the inflammatory infiltration and/or abscess formation along the course of the sinus or fistulous tract from the pyriform fossa to the thyroid gland. In nine patients, CT scans showed the entire course or a part of the sinus or fistulous tract as a tiny spot containing air. MR images showed a sinus or fistulous tract in two patients, whereas sonograms could not depict a sinus or fistulous tract in three patients. All 17 patients were treated with antibiotics. In one patient, the sinus tract was surgically excised, while 15 patients underwent chemocauterization of the sinus or fistulous tract with good outcome. Follow-up was possible for 16 of the 17 patients. CONCLUSION: When an inflammatory infiltration or abscess is present between the pyriform fossa and the thyroid bed in the lower left part of the neck, an infected third or fourth branchial fistula should be strongly suspected.